The relationship between learning goal orientation, goal setting, and performance: a longitudinal study. Issue 8 (19th July 2013) - Taing, Meng U.; Smith, Tiffany; Singla, Neha; Johnson, Russell E.; Chang, Chu‐Hsiang
Abstract In an educational setting, we examined the relationship of learning goal orientation with goal setting and performance over time. At the first time point, we assessed levels of trait learning goal orientation and asked participants to set performance goals. At each follow‐up time point, we reported to participants their current course grade and allowed them to revise their goals. Learning goal orientation was associated with both setting higher goals and maintaining higher performance over time. Additionally, the relationship of learning goal orientation and performance was found to be mediated by goal setting.